Job Satisfaction and Occupational Stress between Private and Public-School Teachers in the Context of Adjustment - Aaditi Karba (CV. Doki Course and Training, 2026)
Teachers play a vital role in the educational system, yet their job satisfaction and mental well-being are strongly influenced by the administrative and structural conditions of their institutions. This study compares job satisfaction and occupational stress among public and private secondary school teachers in Deoghar, Jharkhand, while examining the mediating role of psychological, social, and professional adjustment. Using a quantitative design, standardized psychometric scales were administered to 100 teachers, comprising 50 public and 50 private school educators. The study explores how sector-specific factors including job security, workload, salary, institutional support, and accountability affect teachers’ career satisfaction. Findings suggest that private school teachers experience greater stress due to performance demands and job insecurity, whereas public school teachers face challenges related to administrative workload, large class sizes, and limited resources despite greater job security. The results also indicate that stronger adjustment abilities help reduce the negative effects of occupational stress and improve job satisfaction. These findings highlight the need for sector-specific policies, psychological support, and administrative reforms to reduce teacher burnout and improve the quality of secondary education.